Prospects of life cycle assessment of renewable energy from solar photovoltaic technologies: A review. (November 2018) - Ludin, Norasikin Ahmad; Mustafa, Nur Ifthitah; Hanafiah, Marlia M.; Ibrahim, Mohd Adib; Asri Mat Teridi, Mohd; Sepeai, Suhaila; Zaharim, Azami; Sopian, Kamaruzzaman
Abstract: Life cycle assessment (LCA) is a comprehensive method used to investigate the environmental impacts and energy use of a product throughout its entire life cycle. For solar photovoltaic (PV) technologies, LCA studies need to be conducted to address environmental and energy issues and foster the development of PV technologies in a sustainable manner. This paper reviews and analyzes LCA studies on solar PV technologies, such as silicon, thin film, dye-sensitized solar cell, perovskite solar cell, and quantum dot-sensitized solar cell. The PV life cycle assumes a cradle-to-grave mechanism, starting from the extraction of raw materials until the disposal or recycling of the solar PV. Three impact assessment methods in LCA were reviewed and summarized, namely, cumulative energy demand (CED), energy payback time (EPBT), and GHG emission rate, based on data and information published in the literature. LCA results show that mono-crystalline silicon PV technology has the highest energy consumption, longest EPBT, and highest greenhouse gas emissions rate compared with other solar PV technologies. Highlights: Mono-Si indicated the highest energy, longer EPBT and excessive GHG emissions contribution. DSSC shows the lowest energy requirement and shorter EPBT among other PV technologies. EPBT depends on solar irradiation, module efficiency and lifetime, and type of technology. Differences in GHG emissions rates were caused by energy mix for each countries, solar irradiations and lifetime of PV technologies.